Financial Feasibility Analysis of Carbon Credit-Based Mangrove Forest Restoration Project (Case Study: Mahkota Mangrove Indonesia, Indramayu, West Java) - Mulyati, Widia; Nainggolan, Yunieta Anny; Suryana, Dadang (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to fill the gap in the financial feasibility study of FOLU-based carbon projects by using a case study of a carbon credit-based mangrove forest restoration project initiated by Mahkota Mangrove Indonesia (Mangrovin) in Indramayu, West Java in an area of ??340 hectares. A descriptive quantitative approach is used in this study by applying financial modeling methods, including Net Present Value (NPV), Internal Rate of Return (IRR), and Discounted Payback Period (DPBP). Data were obtained through primary and secondary sources. Common allometric equations from Komiyama et al. (2005) are used to calculate the carbon sequestration potential which is then converted into carbon credits considering project emissions and uncertainty buffers. Cash flows for 30 years are projected using discounting based on green bond and SRI yields. The results of the analysis show strong financial feasibility with an NPV of IDR 223 billion, an IRR of 25.18%, and a DPBP of 7 years. It is known that WACC and revenue factors have the greatest influence on NPV based on sensitivity analysis. A change of ±20% WACC has impact of 30.9% and -23% on NPV, meanwhile revenue factors have an impact of ±24.1%-24.5% on NPV.